2018
DOI: 10.1542/hpeds.2017-0195
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Malnutrition on the Risk of Unplanned 7-Day Readmission in Pediatrics

Abstract: The statistical interaction effect revealed that a patient's risk of readmission is jointly modified by the patient's age and malnutrition status. This finding advances our understanding of the complex picture of the simultaneous risk factor of unplanned 7-day readmissions in pediatrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
2
25
1
Order By: Relevance
“…The pRI, as a continuous measure of general patient condition, considers the vital signs, laboratory results, and nursing assessment results that may be direct or proxy risk factors of readmission. For example, previous research has revealed that there is an association between malnutrition and risk of readmission, 23,24 and the pRI considers a nursing assessment for food sufficiency. Consequently, in addition to being a measure of general patient condition, the pRI encapsulates a range of clinical data that may modify a patient' s risk of readmission.…”
mentioning
confidence: 99%
“…The pRI, as a continuous measure of general patient condition, considers the vital signs, laboratory results, and nursing assessment results that may be direct or proxy risk factors of readmission. For example, previous research has revealed that there is an association between malnutrition and risk of readmission, 23,24 and the pRI considers a nursing assessment for food sufficiency. Consequently, in addition to being a measure of general patient condition, the pRI encapsulates a range of clinical data that may modify a patient' s risk of readmission.…”
mentioning
confidence: 99%
“…True validity of the AMC against a “gold standard,” such as SGA, has not yet been published and is clearly needed. Notwithstanding the need for further validation work, the use of the AMC and the PMI tools has been useful in measuring malnutrition in hospitalized adult and pediatric patients and linking that condition with important clinical outcomes, including mortality, hospital length of stay (adults), complications (pediatrics), and readmissions . .…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric population, similar results have been observed with 3 published studies to date evaluating malnutrition as identified by the PMI and outcomes (see Table 6). [46][47][48] Increased odds of 30-day complications following surgery in children with Crohn's disease was demonstrated in those identified as mildly, moderately, or severely malnourished using the z-score BMI single indicator. 46 This was observed only in mild (OR = 2.1 [P = 0.04]) and severely (OR 3.3 [P = 0.03]) malnourished patients.…”
Section: Malnutrition Characteristics and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Logistic regression is an integral part of data analysis focused on exploring the strength and direction of associations between a dichotomous response variable and a set of potential predictors, and is widely used by researchers [1], [2], [3], [4], [5], [6]. In general, the goal of these research studies is to identify the set of true predictors that are incorporated in the final model which is used for classification, prediction or interpretation.…”
Section: Introductionmentioning
confidence: 99%